Acute effects of high load vs. low load combined with blood flow restriction on explosive performance and muscle-tendon unit mechanical properties - Junjie Zhang (PLoS ONE, 2026)
This study examined the acute effects of high-load resistance training and low-load resistance training with blood flow restriction on sprint ability, pennation angle and lower limb muscle stiffness. A randomized crossover trial was conducted in 17 collegiate male sprinters. Four intervention conditions were applied: high-load (90% 1RM hip thrust [HT] or half-squat [HS]) and low-load (30% 1RM HT or HS with blood flow restriction [BFR]) protocols. Muscle–tendon stiffness, pennation angle, and 20-m sprint performance were assessed at 5 minutes post-intervention. The results showed that statistically significant differences were observed among interventions (p < 0.05). Regarding sprint performance, the 30% HT + BFR significantly improved 0-20m sprint time, whereas the 30% HS + BFR significantly improved 10-20m sprint time compared to high-load conditions. In terms of muscle architecture, both 30% HS + BFR and 90% HS conditions elicited a significant decrease in the pennation angle of the rectus femoris. Moreover, muscle-tendon stiffness generally increased following conditioning activities; notably, the 30% HT + BFR condition increased rectus femoris stiffness, while the 30% HS + BFR condition significantly increased stiffness in the gastrocnemius and Achilles tendon compared to other interventions or baseline. In conclusion, this study demonstrates that low-load resistance exercise combined with blood flow restriction produces greater acute improvements in sprint performance in male sprinters than high-load training, accompanied by reductions in pennation angle and increases in muscle-tendon stiffness.